2019
DOI: 10.1039/c8cc07536k
|View full text |Cite
|
Sign up to set email alerts
|

The capricious nature of iodine catenation in I2excess, perovskite-derived hybrid Pt(iv) compounds

Abstract: Perovskite-derived hybrid platinum iodides with the general formula A2PtIVI6 (A = formamidinium FA and guanidinium GUA) accommodate excess I2 to yield hydrogen-bond-stabilized compounds where the I2 forms catenates with I− anions on the PtI6 octahedra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…In this crystal structure, I 3 À bridges the PtI 6 2À units, thus forming infinite chains with R XB = 0.88 and ∡ Pt-I-I = 179°(see Figure 10a). [41] Another example is depicted in Figure 10b, showing the self-assembled chain-motif of bis(m 2 -iodo)-tetraiodo-di-tellurium (R XB = 0.92, ∡ Te-I-I = 170°). [42] Polyhalides represent another class of inorganic compounds showing halogen bonding involving anionic counterparts.…”
Section: Aexb In the Solid State And In Solutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this crystal structure, I 3 À bridges the PtI 6 2À units, thus forming infinite chains with R XB = 0.88 and ∡ Pt-I-I = 179°(see Figure 10a). [41] Another example is depicted in Figure 10b, showing the self-assembled chain-motif of bis(m 2 -iodo)-tetraiodo-di-tellurium (R XB = 0.92, ∡ Te-I-I = 170°). [42] Polyhalides represent another class of inorganic compounds showing halogen bonding involving anionic counterparts.…”
Section: Aexb In the Solid State And In Solutionmentioning
confidence: 99%
“…[43] The analogous Br 4 2À also WUJGAM [13] 8 I I À 3.331 0.797 177.5 WUJGIU [13] 8 I Cl À 3.022 0.797 173.6 I Cl À 3.051 0.805 175.2 WUJGOA [13] 8 I I À 3.337 0.806 177.6 I I À 3.416 0.817 171.8 FUWFOV [15] 17 I I À 3.920 0.938 169.0 TUPKIZ [39] 18 Br I À 3.637 0.930 172.4 DISJOE [40] 19 Cl NO 3 À 3.137 0.959 145.9 ). [41] b) Self-assembled chains of bis (triethylhydroxyphosphonium) bis(triethylphosphine oxide) bis(m 2 -iodo)-tetraiodo-di-tellurium (Ref.…”
Section: Aexb In the Solid State And In Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halogen bonding has emerged as an important interaction in supramolecular chemistry, [1] and continues to be of great current interest regarding its theoretical description [2] and in fields of application from catalysis [3] to material science [4] and biochemistry. [5] Metal halide complexes can also be used in the construction of supramolecular aggregates involving halogen bonds, serendipitously or by design when halogenated solvents like halomethanes are used, [6,7] in many polyhalide compounds [8][9][10][11][12][13][14][15] or through addition of typical halogen bond donors like tetraiodoethylene (TIE) or 1,4diiodotetrafluorobenzene. [16][17][18][19] A recent example by the Huber group has also shown that the activation of metal halide bonds through halogen bonding is important in homogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…14 The particular motivation for developing B-site vacancy chemistry comes from the prospect for exploiting such vacancies to tune B-site oxidation state, promote low-coordination intercalation, and/or amplify anion-anion interactions. 15 Given the recent discovery that B-site cation substitution is straightforwardly achieved in formate perovskites, we were interested to establish whether this family might support B-site vacancies. An obvious strategy is to employ B n+ cations with charges n > 2: since the organic A-site cation is nearly always monovalent, charge balance could be achieved by reducing the B-site occupancy to 2/n.…”
mentioning
confidence: 99%